Zdrowie Psychiczne w żegludze transoceanicznej = Mental Health in transoceanic sailing - Czarnecki, Mariusz Julian (Journal of Education, Health and Sport, 2016)
Czarnecki Mariusz. Zdrowie Psychiczne w żegludze transoceanicznej = Mental Health in transoceanic sailing. Journal of Education, Health and Sport. 2016;6(7):113-122. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.57188 http://ojs.ukw.edu.pl/index.php/johs/article/view/3656 https://pbn.nauka.gov.pl/sedno-webapp/works/735206 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 25.05.2016. Revised 25.06.2016. Accepted: 28.06.2016. Zdrowie Psychiczne w żegludze transoceanicznej Mental Health in transoceanic sailing Mariusz Czarnecki mariusz.czarnecki@student.umed.wroc.pl Zakład Medycznych Nauk Społecznych Uniwersytetu Medycznego we Wrocławiu Abstrakt Wprowadzenie Stres Kapitana w żegludze transoceanicznej jest nieunikniony. Wpływ stresu na zdrowie osób, które wykonują zawód wymagający wielkiej odpowiedzialności za zdrowie i życie innych, taki jak konsultant medyczny, pielęgniarka, strażak, jest niepodważalny[i] [ii] [iii]. Samoświadomość występowania stresorów oraz sposobów radzenia sobie w sytuacjach skrajnych, przekłada się na potencjał zdrowia osób uprawiających zawód Kapitana[iv]. Cel pracy Określenie głównych stresorów towarzyszących osobom wykonującym zawód Kapitana w żegludze turystycznej, w tym wykazanie poziomu wiedzy na temat stresu i jego wpływu na zdrowie, decyzje oraz wykazanie sposobów radzenia sobie ze stresorami przez badanych. Materiał i metody W badaniu został wykorzystany narracyjny wywiad ekspercki, jako jedna z metod stosowanych w badaniach jakościowych. Został on przeprowadzony z celowo wybraną grupą Kapitanów, za pomocą otwartych wywiadów pogłębionych. W badaniu wzięło udział 5 Kapitanów w stopniu minimum Kapitana Jachtowego, a najwyższym stopniem był stopień Kapitana Żeglugi Wielkiej. Doświadczenie morskie zostało uwzględnione na podstawie wykazanych przez badanych odbytych mil morskich, których zakres wynosił od 20 000 do 200 000 mil morskich. Badania przeprowadzono w okresie lat 2013-2014, ze względu na ograniczony czas przebywania grupy badanej na lądzie. Po skompletowaniu materiał badawczego, została przeprowadzona indywidualna analiza wypowiedzi badanych oraz analiza grupowa służąca generalizacji trendów oraz postępowań u badanej grupy. Każdy z uczestników wyraził pisemną zgodę na udział w badaniu. Wyniki W przeprowadzonym badaniu szczególną uwagę zwrócono na wymienione przez Kapitanów rodzaje stresorów występujących podczas żeglugi oceanicznej. Dodatkowo omówiono poziom postrzegania i radzenia sobie ze stresem w badanej grupie, oraz świadomość zachowania prozdrowotnego mającego wpływ na potencjał zdrowia. Wnioski Osoby pełniące funkcję Kapitana na rejsach oceanicznych, wykazały się znajomością własnych stresorów towarzyszących podczas żeglugi. Dodatkowo wykazały się działaniami prowadzącymi do zachowania potencjału zdrowotnego. Osoby badane nie wykazały reakcji antyzdrowotnych i tendencji prowadzących do wystąpienia skutków powodowanych przez dystres. Słowa kluczowe: zdrowie psychiczne, stres, potencjał zdrowotny, żeglarstwo. Abstract Introduction The awareness of the stressors and how to cope with stressful situations has an impact on the health of people who practice the professions associated with a great responsibility for the health and lives of others, such as, medical consultants, nurses and firefighters. Practising the profession of yacht captain is associated with responsibility for the crew and a sailing vessel in various conditions, and therefore is inseparably linked with the occurrence of stressful situations. To the best of our knowledge, so far, little studies, in terms of stress, were conducted on captains, taking long cruises, such as transoceanic sailing,. Materials and methods In the presented work, 5 captains were studied. The qualitative research, with the use of an expert narrative interview, was used. The open-depth interviews with selected group of captains were performed, with a particular attention to the, indicated by responders, stressors occurring during transoceanic sailing. In addition, the level of perception and coping with stress in the study group, and awareness of healthy behaviour, affecting health of responders were discussed. Results The responders demonstrated the knowledge of the stressors associated with their profession. In addition, they demonstrated the ability to take action, aimed to preserve the health potential. Moreover, the subjects showed no unhealthy tendencies leading to the effects caused by distress. Conclusions The presented studies have confirmed the presence of stressors in the captain profession, however experienced captains showed high level of coping with stressful situation, proving their good and multidirectional training in their profession, also from psychological point of view. The scaled-up studies should be however incorporated into future research, including more developed tools to evaluate the intensity of individual stress and distress in captains. Key words: Naval Medicine, Stress Psychological, Mental Health, Sailors.